The use of data envelopment analysis to assess the R&D effectiveness of the Czech manufacturing industry - Docekalova, Marie; Bockova, Nina (Business: Theory and Practice, 2013)
The article deals with the application of Data Envelopment Analysis on research and development (R&D) effectiveness assessment of Czech manufacturing industry. The aim of this paper is to analyze effectiveness of resources spent in R&D, i.e. how effectively are resources transformed into marketable outputs of R&D. As variables are used R&D personnel, R&D expenditure and Sales of products of R&D to another entity. Data envelopment analysis is based on assessing the quantity of consumed inputs by the produced outputs and estimation of production possibility frontier by techniques of linear programming. Two models are calculated: an input oriented model with variable returns to scale and an input oriented model with constant returns to scale. Described approach to evaluation of R&D effectiveness can also be used in other sectors of economy as well as other countries. It was found that the most effective sector of Czech manufacturing industry is a manufacture of wood and paper while automotive industry is the least effective.